1998
DOI: 10.1046/j.1365-2982.1998.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the optimal parameters for recording cortical evoked potentials to human oesophageal electrical stimulation

Abstract: Cortical evoked potentials in response to stimulation of the oesophagus may prove to be a powerful technique for assessing the oesophageal afferent pathway in health and disease. However, in order to maximize the potential of this technique it is essential that the optimal parameters for recording oesophageal CEP are established. The aim was to determine the optimal parameters required to record reproducible CEP. CEP were recorded from the vertex in eight subjects (age range 23-44 years). Electrical stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 28 publications
3
68
0
Order By: Relevance
“…The protocols for esophageal and chest evoked potentials differed slightly because the esophageal stimulation intensity used to evoke the cortical responses was always calculated as a percentage of the subject's pain threshold on that particular day (15). As pain thresholds increased between visits, then the stimulation intensity used also increased, and this was reflected by a reduction in the latency of some evoked potential components, which is commonly seen when the stimulation intensity is increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocols for esophageal and chest evoked potentials differed slightly because the esophageal stimulation intensity used to evoke the cortical responses was always calculated as a percentage of the subject's pain threshold on that particular day (15). As pain thresholds increased between visits, then the stimulation intensity used also increased, and this was reflected by a reduction in the latency of some evoked potential components, which is commonly seen when the stimulation intensity is increased.…”
Section: Discussionmentioning
confidence: 99%
“…EEP were recorded by averaging a total of 200 esophageal stimuli, acquired at a frequency of 0.2 Hz, during four runs of 50 stimuli, with a 10-min interrun interval. The parameters used were selected on the basis of our previous work to provide optimal EEP responses (15). After each run of 50 stimuli, the subjects were asked to score the esophageal sensation experienced using a six-point categorical rating scale: 1, Unaware; 2, Slight sensation; 3, Definite sensation; 4, Slight Discomfort; 5, Uncomfortable; and 6, Painful.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported significant correlations (up to .83) between the heartbeat perception score and different cardiodynamic parameters, that is, stroke volume, blood ejection velocity, momentum of the ejected blood mass, and contractility. For external stimuli (visual, auditory, somatosensory), it is a wellestablished fact that the stimulus intensity influences the amplitudes of the evoked potentials (e.g., Carrillo-de-la-Pena, Rodriguez Holguin, Corral, & Cadaveira, 1999;Cass & Polich, 1997;Covington & Polich, 1996;Nakajima & Imamura, 2000 O. Pollatos and R. Schandry studies with esophageal-evoked potentials showed that an increase of stimulus intensity was associated with an increase in the amplitude of the esophageal-evoked potential components (Fallen et al, 2001;Hobson et al, 1998Hobson et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, patients suffering from irritable bowel syndrome report lower pain detection threshold to colorectal distension than healthy volunteers (29,35), indicating that the model is sensitive to underlying pathophysiology. An improved translational model includes the use of cerebral evoked potentials (CEPs) to objectively assess the brain response to colorectal distension in animals and humans (16,19,20,33,37,38). In previous studies, electrically elicited CEPs from the gut have been favored, compared with balloon distension, because this stimulus is easier to control with respect to localization, onset, and duration.…”
mentioning
confidence: 99%